Mechanization of Potato Production in the Libyan Jamahiriya: II. Effect of Seed Tuber Sizes on Mechanical Planting Efficiency, Labor Requirement, Seed Tuber Rate and Y ield - SHERIF, SHARAFEDDIN M.; CHAUDHRY, MUHAMMAD S. (The Libyan Journal of Agriculture, 2023)
An experiment was conducted at the Faculty of Agriculture Farm. University of Al-Fateh. Tripoli. S.P.L.A.J., during the spring of 1977. The objective was to study the effects of seed tuber sizes on the mechanical planting efficiency, labor requirement, seed rate and the yield. Mechanical planting of small seed tubers (35-45 mm) and halves of large seed tubers (45-60 mm) was efficient and labor saving than the planting of large seed tubers. The latter plugged the planter and reduced the planting capacity. The weight of small and halves of large size seed tubers planted per hectare was 28 and 43% less than the large seed tubers. Sprouting time and tuber yield was significantly affected by the potato cultivars. Arran Banner took significantly less time to sprout compared to Mirka and Vittorini. The sequence was: Arran Banner < Mirka < Vittorini. Tuber yield of Cv. Arran Banner was significantly higher than Mirka and Vittorini. The order of yields was: Arran Banner > Mirka = Vittorini. Sprout emergence and tuber yields were not affected by the seed tuber sizes. Potato cultivars and seed tuber sizes exhibited no interaction for sprout emergence and the tuber yield.